Exploring the interplay of academic stress, motivation, emotional intelligence, and mindfulness in higher education: a longitudinal cross-lagged panel model approach - Shan Zhang; Shazia Rehman; Yali Zhao; Erum Rehman; Bushra Yaqoob (BMC Psychology)
Abstract Students in higher education often encounter significant academic pressure, which can have profound implications for their mental health and academic performance. The current study employs a two-wave longitudinal design to investigate the dynamic interrelationships among academic stress, academic motivation, emotional intelligence, and mindfulness. The study employed a cross-lagged panel model to investigate the temporal interactions among these four constructs and their influence on the academic experiences of doctoral students. The sample consisted of 643 individuals at Time 1 (September/October 2022), followed by a subsequent assessment involving 413 participants (July/August 2023). Notably, there was an overlap of 373 participants who were evaluated at both time points. The results indicated the presence of substantial reciprocal relationships among the constructs under investigation. The outcomes indicated that elevated emotional intelligence and mindfulness levels are associated with reduced academic stress and enhanced motivation. The implications of this analysis underscore the necessity of facilitating interventions aimed at enhancing emotional intelligence and mindfulness. These components are instrumental in promoting resilience and supporting academic success among students. These longitudinal insights hold significant importance within the academic literature as they elucidate the various stressors doctoral students encounter. Furthermore, this research provides practical implications for educators and policymakers in formulating targeted strategies to enhance student well-being and improve educational outcomes.